Influence of relative velocity and contact force between abrasive media and workpiece on material removal in gyro finishing. (July 2022) - Ohlert, Marius; Brüssel, Fabian; Prinz, Sebastian; Barth, Sebastian; Bergs, Thomas
Abstract: Gyro finishing is capable of reducing the surface roughness and inducing residual compressive stresses into the edge zone of the component to enhance the fatigue strength. Due to an insufficient understanding of gyro finishing processes, it is not possible to adjust the process result in a knowledge-based manner. In order to understand the mechanisms of action in the process, knowledge of the contact between abrasive media and workpiece is necessary. This paper presents the analysis of the contact conditions and the process state variables between abrasive media and workpiece with two measuring systems. Furthermore, the influence of the contact conditions and the process state variables on the material removal mass was investigated. Therefore, analogy workpieces were machined by gyro finishing using different process state variables and abrasive media specifications. Based on the results, an empirical-analytical model is derived, which is able to describe the material removal mass depending on the contact conditions and the process state variables between abrasive media and workpiece.